The voltage‐gated sodium channel NaV1.9 in visceral pain. Issue 3 (14th October 2015) - Hockley, J. R. F.; Winchester, W. J.; Bulmer, D. C.
Abstract: Background: Visceral pain is a common symptom for patients with gastrointestinal (GI) disease. It is unpleasant, debilitating, and represents a large unmet medical need for effective clinical treatments. Recent studies have identified NaV 1.9 as an important regulator of afferent sensitivity in visceral pain pathways to mechanical and inflammatory stimuli, suggesting that NaV 1.9 could represent an important therapeutic target for the treatment of visceral pain. This potential has been highlighted by the identification of patients who have an insensitivity to pain or painful neuropathies associated with mutations in SCN11A, the gene encoding voltage‐gated sodium channel subtype 1.9 (NaV 1.9). Purpose: Here, we address the role of NaV 1.9 in visceral pain and what known human NaV 1.9 mutants can tell us about NaV 1.9 function in gut physiology and pathophysiology. Abstract : Visceral pain and hypersensitivity are symptoms of patients with gastrointestinal diseases such as irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD). Recent evidence implicates the voltage‐gated sodium channel subtype 1.9 (NaV 1.9) as a regulator of primary visceral nociceptor sensitivity and as a contributor to sodium current conductance in neurones of the enteric nervous system. Patients with painful and painless phenotypes associated with mutations in NaV 1.9 have been identified, which, in some cases, possess complex gastrointestinal disorders. These studies have served to confirm a key role for NaV 1.9 in visceral pain and suggest that NaV 1.9 may contribute to gastrointestinal disorders.